Analysis of stator current of induction motor used in transport system at single phasing by measuring phase angle, symmetrical components, Skewness, Kurtosis and harmonic distortion in Park plane. Issue 1 (1st March 2014) - Chattopadhyay, Surajit; Chattopadhyaya, Aveek; Sengupta, Samarjit
Abstract : Stator current of induction motor is analysed at single phasing by measuring phase angle, symmetrical components, Skewness, Kurtosis and harmonic distortion in Park plane. Diagnosis of single phasing of induction motor has been achieved by sequence components and stator current based pattern assessment. Distinct phase shift from 120° to 180° is observed between healthy phases. Patterns are formed using line currents and single phasing is assessed by using rule sets developed from features extracted from those patterns. Experimental result agrees with rule set and result obtained by assessment using sequence components. Then assessment is done by analysing wavelet decomposition based Skewness and Kurtosis of stator current in Park plane. At last, area based approach is used for assessment of single phasing and different distortion factors because of harmonics in Park plane are assessed. Accuracy increases with the increase of sampling rate of data acquisition system and use of Park plane has reduced computation effort by two‐thirds. Thus single phasing is detected by sequence components supported by pattern formation and feature extraction and then harmonics during single phasing are assessed by wavelet decomposition and area‐based approach in Park plane.